2021
DOI: 10.1016/j.jlr.2021.100084
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the available cholesterol concentration in the inner leaflet of the plasma membrane of mammalian cells

Abstract: Cholesterol is an essential component of the mammalian plasma membrane involved in diverse cellular processes. Our recent quantitative imaging analysis using ratiometric cholesterol sensors showed that the available cholesterol concentration in the inner leaflet of the plasma membrane (IPM) is low in unstimulated cells and increased in a stimulus-specific manner to trigger cell signaling events. However, the transbilayer distribution of cholesterol in the plasma membrane of mammalian cells remains controversia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 85 publications
(183 reference statements)
2
31
0
Order By: Relevance
“…Given these considerations, we propose that the outer leaflet pool of cholesterol, especially in the SM-rich ciliary membrane ( Kinnebrew et al, 2019 ), is a more plausible target of regulation by PTCH1 to control SMO activity. We emphasize that our model for PTCH1 function does not depend on (and does not inform) the outcome of current debates around the distribution of cholesterol between the inner and outer leaflets of the plasma membrane ( Buwaneka et al, 2021 ; Courtney et al, 2018 ; Liu et al, 2017 ; Steck and Lange, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given these considerations, we propose that the outer leaflet pool of cholesterol, especially in the SM-rich ciliary membrane ( Kinnebrew et al, 2019 ), is a more plausible target of regulation by PTCH1 to control SMO activity. We emphasize that our model for PTCH1 function does not depend on (and does not inform) the outcome of current debates around the distribution of cholesterol between the inner and outer leaflets of the plasma membrane ( Buwaneka et al, 2021 ; Courtney et al, 2018 ; Liu et al, 2017 ; Steck and Lange, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…These modified PFOD4 probes do not differentiate between accessible and inaccessible pools of cholesterol since their binding to cholesterol-containing vesicles is insensitive to the presence of SM or other phospholipids ( Liu et al, 2017 ). To avoid the complications associated with using these probes to measure membrane cholesterol accessibility ( Buwaneka et al, 2021 ; Courtney et al, 2018 ; Steck and Lange, 2018 ), we sought to measure outer leaflet accessible cholesterol using a completely independent method. Our TIRFM assay uses the TdTomato-PFOD4H probe to simply monitor the cholesterol content of the inner leaflet; cholesterol accessibility in the outer leaflet is assessed by the rate of cholesterol transfer from the membrane to MβCD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a decrease in the IPM cholesterol level was also examined by TIRF microscopy using PFO-D4H, which has a higher affinity for cholesterol than wild-type PFO-D4 (Maekawa and Fairn, 2015). To observe a change in the IPM cholesterol level, we established HeLa cells expressing a proper level of GFP-D4H, because the expression level of the cholesterol probe greatly affects its translocation to the PM (Buwaneka et al, 2021). When the cells were transiently transfected with ABCA1-mCherry and cultured in the presence of PSC-833, GFP-D4H gradually dissociated from the PM of the cells expressing ABCA1-mCherry after removing PSC-833 to exert ABCA1 activity, but in other cells without ABCA1 expression, GFP-D4H stayed at the PM (Figure 3b).…”
Section: Resultsmentioning
confidence: 99%
“…However, very recently, Cho's group showed that the IPM cholesterol level is much lower than the OPM cholesterol level by quantitative imaging analysis using two different types of ratiometric cholesterol sensors that are not appreciably affected by changes in the lipid environmental (Buwaneka et al, 2021). Some IPM cholesterol molecules are sequestered by membrane proteins such as Caveolin-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation